TENDENCY OF AORTIC DISEASES IN VIETNAM NATIONAL HEART INSTITUTE IN 2024 – 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the clinical characteristics of aortic diseases and the management approaches to these conditions at the Cardiovascular Institute, Bach Mai Hospital.Methods: All patients admitted between August 2024 and August 2025 were included, comprising both emergency and non-emergency cases.Results: Based on a one-year study of patients with aortic disease, with analysis stratified by two age groups (60 years), the findings showed that aortic disease predominantly occurred in older patients, with a mean age of 65.3 ± 9.4 years. Male patients were more commonly affected than female patients (76% vs. 24%). Hypertension was the leading risk factor (86.3%), and the most common presenting complaints were chest pain or abdominal pain. In patients aged 60 years, abdominal aortic aneurysm was the most common diagnosis (50.9%). Regarding treatment strategy, aggressive open surgical repair was performed more frequently in patients aged 60 years, conservative management and minimally invasive endovascular intervention were more commonly selected, accounting for 59.6% and 34.8%, respectively.Conclusion: Aortic disease predominantly affects older male patients, with hypertension being the most prominent risk factor. Clear differences were observed in both disease pattern and treatment strategy between the two age groups: patients aged 60 years were more likely to have abdominal aortic aneurysm and to receive conservative treatment or minimally invasive endovascular intervention. These findings suggest that age plays an important role in guiding diagnosis and treatment selection in patients with aortic disease.
Keywords: aortic aneurysm, aortic dissection, aortic surgical repair, endovascular aortic repair.